Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.1007/s10534-014-9722-y
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic trioxide induced indirect and direct inhibition of glutathione reductase leads to apoptosis in rat hepatocytes

Abstract: Glutathione reductase (GR) is an essential enzyme which maintains the reduced state of a cell. Therefore GR malfunction is closely associated with several disorders related to oxidative damage. The present study reports toxic manifestation of arsenic trioxide in respect of GR leading to apoptosis. Isolated rat hepatocytes exposed to arsenic trioxide were analyzed for GR expression and activity. Arsenic resulted in a time dependent inhibition of GR mediated by the superoxide anion. The cellular demand of functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 33 publications
1
9
0
Order By: Relevance
“…DNA damage, PARP cleavage and inhibition of glutathione reductase followed by caspase activation are the marks of cell response to ATO treatment [44]. Our analysis of the DNA damage through evaluation of γ-H2AX histone expression showed that NP realgar and ATO exhibit similar effects preferentially at higher concentration tested.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…DNA damage, PARP cleavage and inhibition of glutathione reductase followed by caspase activation are the marks of cell response to ATO treatment [44]. Our analysis of the DNA damage through evaluation of γ-H2AX histone expression showed that NP realgar and ATO exhibit similar effects preferentially at higher concentration tested.…”
Section: Discussionmentioning
confidence: 70%
“…This myeloid leukemia cell line is often used as a model for terminal hematopoietic differentiation that could be started by realgarinduced increase of intracellular glutathione followed later by the decline to minimum at 6 h. Our study in BOWES and A375 cells revealed the increase of intracellular GSH level at 24 h of the treatment, possibly mediated by the upregulation of NRF2 mRNA as well as its downstream target HO-1, similarly to the reported increase of HO-1, Nrf2, and NFκB in endothelial cells treated by ATO [43]. These results also support the assumption that despite different physical forms of particulate and soluble arsenic, mechanisms of their action are very similar.DNA damage, PARP cleavage and inhibition of glutathione reductase followed by caspase activation are the marks of cell response to ATO treatment [44]. Our analysis of the DNA damage through evaluation of γ-H2AX histone expression showed that NP realgar and ATO exhibit similar effects preferentially at higher concentration tested.…”
mentioning
confidence: 70%
“…Apoptosis is one of the important pathophysiological hallmarks of liver aging and age‐related liver diseases 33,34 . Arsenic‐induced apoptosis has been determined in hepatic tissues and primary hepatocytes 15,16 . However, the potential mechanism of that is still unclear and no effective therapeutic agents have been found.…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological studies have shown that there is high prevalence of arsenicosis such as skin, 9,10 liver, 11 kidney, 12 lung, 13 and bladder damage 14 . Liver, as one of the important target organs of arsenic toxicity, exhibits an increase of hepatocyte apoptosis in hepatic tissues and primary hepatocytes 15,16 . However, the apoptosis mechanism involved in arsenic poisoning remains unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Reagents were added to either the clarified homogenized cell culture containing mAb or to the mAb alone. For enzyme inhibition studies, the concentrations were chosen based on the enzyme's known Ki or IC50 values or according to published references (Grinblat, Sreider, & Stoppani, 1989;Ray, Chatterjee, Mukherjee, & Bhattacharya, 2014;Rigobello et al, 2004;Sadhu, Callegari, Zhao, Guan, & Seefeldt, 2013;Shantz, Talalay, & Gordon, 1989). The TrxR, GR, and Grx inhibitors (ATM, 2-AAPA, nitrofurantoin (NFT), and AsO 2 ) were used at a final concentration of 0.075 mM.…”
Section: Sample Treatment and Purificationmentioning
confidence: 99%